2012
DOI: 10.1016/j.juro.2012.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Endoscopic Laser Excision of Polypropylene Mesh/Sutures Following Anti-Incontinence Procedures

Abstract: word count: 280 Manuscript word count (including abstract): 2380 Number of references: 19 Number of tables: 3 Number of figures: 1 Abstract Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…This was first reported in 2004 by Hodroff et al 10 It is another minimally invasive technique with rapid recovery but the reported success of complete mesh removal in some series is low and there seems to be a high recurrence rate (Table 1). Davis et al 12 reported on 12 patients which is the largest series. Four patients (33%) required a second endoscopic procedure for residual mesh removal and one required an open procedure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This was first reported in 2004 by Hodroff et al 10 It is another minimally invasive technique with rapid recovery but the reported success of complete mesh removal in some series is low and there seems to be a high recurrence rate (Table 1). Davis et al 12 reported on 12 patients which is the largest series. Four patients (33%) required a second endoscopic procedure for residual mesh removal and one required an open procedure.…”
Section: Discussionmentioning
confidence: 98%
“…3,4 Various surgical techniques have been reported for mesh removal. [3][4][5][6] The most widely reported is the transurethral approach either using electrocautery for division/resection of the tape 7,8 or Holmium Laser [9][10][11][12] . This approach although minimally invasive has a high rate of incomplete mesh removal and recurrence of mesh exposure and symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, this study 6 excluded patients whose slings were removed owing to pain and other indications, thus the actual incidence of sling removal owing to complications is probably even higher than that. Extrapolating from this estimate and the estimated number of slings implanted in the 6,9,10,41,44,[100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] Use of imperfect research methodologies, a lack of long-term follow up and reporting bias have been suggested as causes of these differences. 10,45,115,116 Safety and risk:benefit considerations Safety of SMUS surgery refers to the probability of any adverse event, while risk describes the range and probability of specific adverse events.…”
Section: Smus Complicationsmentioning
confidence: 99%
“…Rafique described various reported techniques and cystoscopic modification of intravesical stone retrival [1]. Though use of Holmium: YAG laser to fragment and facilitate transurethral removal of large intravesical foreign bodies have been described [11,12], but with fragmentation, there is always a possibility of incomplete removal and subsequent recurrence of stone.…”
Section: Typementioning
confidence: 99%